2666 - Bolano, Roberto 1953-2003; Wimmer, Natasha (New York Farrar, Straus and Giroux, 2008)
An American sportswriter, an elusive German novelist, and a teenage student interact in an urban community on the U.S.-Mexico border where hundreds of young factory workers have disappeared.
The part about the critics -- The part about Amalfitano -- The part about fate -- The part about the crimes -- The part about Archimboldi.
Keywords: Women -- Crimes against -- Fiction; Mexico -- Fiction